New Public Management: Is that for better public services? - Hartanti Dewi; Hendra Sahputra; Zulfikar Zulfikar (Institute of Computer Science (IOCS), 2023)
The presence of a state is for the welfare of its citizens. All the basic needs of citizens can be fulfilled and the basic rights of the community can be maintained or even provided by a state. New Public Management (NPM) is a tool that helps a country reform its government institutions. This reform process is a step of change that will lead to the provision of better public services. The results of this study indicate that NPM is only a supporting tool that cannot be drawn a uniform line in its application because in the end the characteristics of a nation and cultural differences greatly affect how a country implements NPM in their institutions.